Verbascoside Inhibits the Activation of NLRP3 Inflammasome and Improves BV-2 Cell Inflammatory Damage - Wenjing HUANG; Fang CHENG; Min DU; Jiayi CHEN; Wei XIANG; Ke SHI; Xingliang XIE; Yanmei SHENG (Shipin gongye ke-ji)
Objective: To investigate the main component verbascoside (VB) in Osmanthus fragrans which inhibits NLRP3 inflammasome activation to improve inflammatory damage in BV-2 cells and its related mechanisms. Methods: A model of inflammatory damage induced by oxygen-glucose deprivation (OGD) in BV-2 cells was employed. The experiment was divided into 4 groups: The normal control group, the OGD model group, the Osmanthus fragrans ethanol extract group (OGD+OEE), and VB group (OGD+VB). The MTT assay was used to evaluate the effects of the treatments on BV-2 cell viability. The release of lactate dehydrogenase (LDH) in the culture supernatant was measured using an LDH cytotoxicity assay kit to assess the impact on the cell membrane. Hoechst 33342/PI double staining was utilized to examine the effect of the treatments on cell pyroptosis. Furthermore, Western blot analysis was conducted to investigate the expression levels of proteins related to the NLRP3 inflammasome pathway, including NLRP3, Caspase-1, IL-1β, and TNF-α. Results: The MTT assay results indicated that both OEE and VB significantly promoted the viability of BV-2 cells (P<0.001). LDH assay results demonstrated that both OEE and VB markedly reduced the release of LDH in the culture supernatant (P<0.001), indicating reduced damage to the cell membrane. Hoechst 33342/PI double staining revealed a significant decrease in the number of PI-positive cells in both the OEE and VB groups (P<0.01), with a marked reduction in fluorescence intensity. The Western blot results indicated that, after treatment with verbascoside, there was a significant decrease in the levels of cell pyroptosis proteins associated with the NLRP3/Caspase-1/IL-1β signaling pathway (P<0.05 or P<0.01). Conclusion: VB can ameliorate OGD-induced inflammatory damage in BV-2 cells, which may constitute the primary pharmacodynamic basis for the anti-inflammatory effects of OEE. The mechanism is associated with the inhibition of the NLRP3/Caspase-1/IL-1β signaling pathway.